Self-Esteem and Facebook Addicted of High School Students in Bangkok Metropolitan Area - Pholphet, Kwunkao; Tuntasood, Benjaporn (Journal of the Psychiatric Association of Thailand, 2016)
Objectives : To determine Facebook addiction behaviors and its relationship with self-esteem among high school students in Bangkok. Method : This cross-sectional descriptive study was conducted in 6 high schools based on educational service area in Bangkok. The research instruments consisted of the questionnaires regarding demographic characteristics and the patterns of Facebook usage, the Thai version of Bergen Facebook Addiction Scale (Thai-BFAS) and the revised version of Thai Rosenberg Self-Esteem Scale (RSES). The data was analyzed by using percentage, mean, chi-square and multiple logistic regression analysis. Results : Among the 326 participants, 10.4% were addicted to Facebook. Most of them had middle level of self-esteem (65.6%). Others had low level of self-esteem (21.5%) and high level of self-esteem (12.9%). The participants who had the low level of self-esteem were addicted to Facebook more than others, who had high or middle level of self-esteem. There were statistically significant associated factors with Facebook addiction, which were gender, education program, relationship with mother, Facebook usage experience, number of friends, adding partner, adding mutual friends, adding stranger, checking in, chatting, following friends, posting or tagging photo, posting or tagging video and commenting. Moreover, the risk factors of Facebook addiction were the frequency of usage, the frequency of selfie, the frequency of updating status and the average of GPA. Conclusion : Facebook addiction in high school students was found 10.4% and associated with low self-esteem. Therefore, raising self-esteem should be considered for the mental health promotion in order to reduce the Facebook addiction in adolescents.